Corrosion Protection of Offshore Wind Energy Constructions in Germany: Challenges and Approaches - Plagemann, P.; Momber, A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The significant increase in the share of renewable energies within the next decades has high political relevance in Germany. Due to the high availability and rate of yield for wind, offshore wind energy plants are of particular interest. Currently, wind energy plants with power ratings up to 8 MW and rotor blade diameters up to 150 m are raised near the German coast. To operate these devices economically, service lives of 25 years or more are required. Here, corrosion is an important limiting factor, as the devices are constantly exposed to a highly corrosive environment (sea water, saline air). In this paper, general conditions and specific technical challenges to protect offshore wind energy plants from corrosion are described, and some examples of technical solutions are presented. Some of the reported solutions have been developed in nationally funded joint research projects between research institutions and industrial companies, representing the full supply chain for offshore wind energy plants.